Guerra, nação e cinema: uma leitura filmográfica sobre as motivações norte-americanas para a ação beligerante - SILVA, Maurineide Alves da (2011)
The United States is a country of tradition belligerent. It is common to find in their public squares and monuments statues of military figures, in addition to reserve specific days to honor them, military parades and ceremonies are displayed in various regions of the country and numerous film productions are performed representing the U.S. involvement in world conflicts. It is felt that the war is part of its fundamental characteristics. Seeking to understand the aspects that have built this tradition and thus marked the history of the United States military interventions around the world, without limiting ourselves to explanations that emphasize only the imperialist interests, but taking into account ideological and dogmatic aspects, we reach a ideology formulated in the nineteenth century, in order to justify the U.S. right to intervene in another nation: the ideology of Manifest Destiny. The three ideas that form the three show Manifest Destiny of American beliefs that are part of their national identity and profoundly marked its history: Puritanism, democracy and capitalism. To peer into the permanence of these three beliefs motivating the U.S. military interventions in the XXI century and still seek mainly new elements that enrich our historical understanding of the American society in his belligerent relations with other regions of the world, analyze imagery of a document period, the film Black Hawk Down (Black Hawk Down, Hidley Scott, 2001), which refers to U.S. military intervention in Somalia in 1993 and eventually present the vision of its directors on the subject. As one of the forms of cultural expression more representative of the United States, the film ends up a material extremely rich set of information about the beliefs and customs United States.